2006
DOI: 10.1007/s00535-006-1789-y
|View full text |Cite
|
Sign up to set email alerts
|

Activated platelets as a possible early marker to predict clinical efficacy of leukocytapheresis in severe ulcerative colitis patients

Abstract: These results indicate that the therapeutic responses to LCAP were reflected in modulations of population and/or platelet functions, especially after the first session. The decrease of such activated platelets immediately after the first LCAP may be an early marker for predicting the response in patients with severe UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…Recent studies have reported that activated platelets were removed by LCAP [12,13]. The removal of activated platelets was due to their adherence to the filter used in LCAP [27]. Yagi et al [28] reported that removal of activated platelets by LCAP resulted in decrease of platelet-derived MPs, which remained at a low level for 1 month in the case of ulcerative colitis.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have reported that activated platelets were removed by LCAP [12,13]. The removal of activated platelets was due to their adherence to the filter used in LCAP [27]. Yagi et al [28] reported that removal of activated platelets by LCAP resulted in decrease of platelet-derived MPs, which remained at a low level for 1 month in the case of ulcerative colitis.…”
Section: Discussionmentioning
confidence: 97%
“…24 Interestingly, these activated platelets have also increased in patients with active ulcerative colitis and that these cells were reduced after LCAP treatment. 25,26 Therefore, improvement of ESR in the present study might be partially mediated by reduction of increased platelet aggregation activities.…”
Section: Discussionmentioning
confidence: 85%
“…According to this evidence, we have hypothesized that this significant platelet removal achieved during LCAP might have an active role in downregulating severe immunological reactions in patients with UC with an acute flare. We have also proved that activated platelets may have potential to predict clinical efficacy of LCAP in severe UC patients 27 …”
mentioning
confidence: 76%